Factors associated with emotional mental disorders among adolescents - Indri Putri Umairoh; Marta Butar Butar; Helmi Suryani Nasution; Hendra Dhermawan Sitanggang (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: Emotional mental disorders among adolescents are an increasing public health concern. The I-NAMHS survey reported that 34.9% of adolescents experience mental health problems, while a preliminary survey at Senior High School 5 Kota Jambi found that 52.4% of students were indicated to have emotional mental disorders. Purpose: To analyze factors associated with emotional mental disorders among adolescents. Method: A quantitative analytic study with a cross-sectional design was conducted among 200 students selected using proportionate stratified random sampling. Data were analyzed using chi-square tests. Results: Gender (p=0.004; PR=1.64; 95% CI: 1.13–2.37) and bullying (p<0.001; PR=3.04; 95% CI: 1.56–5.95) were significantly associated with emotional mental disorders, while parental involvement was not significantly associated (p>0.05). Conclusion: Gender and bullying were identified as factors associated with emotional mental disorders among adolescents. Keywords: Adolescents; Emotional Mental Disorders; Senior High School.